2023
DOI: 10.3390/ijms241310610
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Linkers’ Influence on Peptide-Based Piezoelectric Biosensors’ Sensitivity to Aldehydes in the Gas Phase

Abstract: Recent findings qualified aldehydes as potential biomarkers for disease diagnosis. One of the possibilities is to use electrochemical biosensors in point-of-care (PoC), but these need further development to overcome some limitations. Currently, the primary goal is to enhance their metrological parameters in terms of sensitivity and selectivity. Previous findings indicate that peptide OBPP4 (KLLFDSLTDLKKKMSEC-NH2) is a promising candidate for further development of aldehyde-sensitive biosensors. To increase the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Serine proteases such as those described above have a central role in a wide array of inflammatory diseases that overlap in their pathology with chronic wounds . Whereas previous studies for protease detection have shown varying degrees of affinity with dependence on linker length, to date, no studies have addressed the role of spacer length and design in the context of biosensor to nanocellulose surface relationship. Prior studies utilized long-chain (up to 10 000 MW) polyethylene glycol (PEG) repeat units or short peptide units to prepare self-assembled monolayers for analyte detection on gold surfaces, typically by surface plasmon resonance or quartz crystal microbalance for piezoelectric response. , In a separate example, an electrochemical assay used a gold substrate and an eight-carbon aliphatic linker, or a PEG moiety containing 2–12 repeat units, to detect bovine serum albumin (BSA) and trypsin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serine proteases such as those described above have a central role in a wide array of inflammatory diseases that overlap in their pathology with chronic wounds . Whereas previous studies for protease detection have shown varying degrees of affinity with dependence on linker length, to date, no studies have addressed the role of spacer length and design in the context of biosensor to nanocellulose surface relationship. Prior studies utilized long-chain (up to 10 000 MW) polyethylene glycol (PEG) repeat units or short peptide units to prepare self-assembled monolayers for analyte detection on gold surfaces, typically by surface plasmon resonance or quartz crystal microbalance for piezoelectric response. , In a separate example, an electrochemical assay used a gold substrate and an eight-carbon aliphatic linker, or a PEG moiety containing 2–12 repeat units, to detect bovine serum albumin (BSA) and trypsin.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies utilized long-chain (up to 10 000 MW) polyethylene glycol (PEG) repeat units or short peptide units to prepare self-assembled monolayers for analyte detection on gold surfaces, typically by surface plasmon resonance or quartz crystal microbalance for piezoelectric response. 27 , 28 In a separate example, an electrochemical assay used a gold substrate and an eight-carbon aliphatic linker, or a PEG moiety containing 2–12 repeat units, to detect bovine serum albumin (BSA) and trypsin. In that context, this study employs cotton cellulose as a nanocellulose-based substrate for both neutrophil and pancreatic elastases.…”
Section: Introductionmentioning
confidence: 99%